The interplay between mutations in cagA, 23S rRNA, gyrA and drug resistance in Helicobacter pylori - Júlia Silveira Vianna; Ivy Bastos Ramis; Daniela Fernandes Ramos; Otávio Leite Gastal; Renato Azevedo da Silva; Carla Vitola Gonçalves; Pedro Eduardo Almeida da Silva (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
ABSTRACT In this study, we evaluated the mutations of Helicobacter pylori associated with resistance to clarithromycin and levofloxacin. Furthermore, based on the proposed interaction between antimicrobial resistance and pathogenicity, we correlated the mutation profiles of the strains with the presence of the pathogenicity gene cagA. We analyzed 80 gastric biopsy specimens from H. pylori-infected patients for point mutations in the 23S rRNA gene region and in the gyrA gene, which are related to clarithromycin and levofloxacin resistance, respectively, and investigated the presence of the cagA gene in these strains. We observed that in the assayed biopsies, 8.7% (7/80) had mutations in the 23S rRNA gene region at positions 2143 and 2142, while 22.5% (18/80) had mutations in gyrA at codons 87 and 91. Moreover, absence of the CagA-EPIYA pathogenicity factor was observed in 68% (17/25) of resistant samples. The knowledge of the local profile of antimicrobial resistance and the complex interplay involving resistance and pathogenicity can contribute to an appropriate clinical approach.